1995
DOI: 10.1111/j.1476-5381.1995.tb15002.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the two enantiomers, S‐16257‐2 and S‐16260‐2, of a new bradycardic agent on guinea‐pig isolated cardiac preparations

Abstract: 1 The electromechanical effects of two enantiomers, S-16257-2 (S57) and S-16260-2 (R60), were studied and compared in guinea-pig isolated atria and ventricular papillary muscles. The possible stereoselectivity of the interaction on the cardiac Na' channel was analysed by comparing the effects of the two enantiomers on the onset and recovery kinetics of the frequency-dependent V,,.S block. 2 In spontaneously beating right atria, S57 and R60 (10-8 M-10-4 M) exerted a negative chronotropic effect (pIC50 = 5.07 ± … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
25
0

Year Published

1996
1996
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 26 publications
4
25
0
Order By: Relevance
“…Such observations are in favour of the absence of significant class III antiarrhythmic activity of the drug. Perez et al (1995) reported that the fast sodium inward current was blocked by S 16257 at concentrations higher than S x 10-6 M. This block probably plays a role in the effects of S 16257 on the activity of Purkinje cells and sinus node subsidiary cells, where INa is present. In the primary pacemaker cells, it has been reported that the fast sodium inward current is absent or not normally activated (Irisawa et al, 1993 …”
Section: U-l Effect Of S 16257 On the Two Types Of Calcium Currentsmentioning
confidence: 99%
“…Such observations are in favour of the absence of significant class III antiarrhythmic activity of the drug. Perez et al (1995) reported that the fast sodium inward current was blocked by S 16257 at concentrations higher than S x 10-6 M. This block probably plays a role in the effects of S 16257 on the activity of Purkinje cells and sinus node subsidiary cells, where INa is present. In the primary pacemaker cells, it has been reported that the fast sodium inward current is absent or not normally activated (Irisawa et al, 1993 …”
Section: U-l Effect Of S 16257 On the Two Types Of Calcium Currentsmentioning
confidence: 99%
“…Effects on cardiac Na + channels 69 and on Kv1.5 potassium channels 70 were reported only in vitro at very high concentrations (30-100 μmol/L), so these nonspecific effects seem unlikely to arise at therapeutically relevant concentrations, as in clinical practice. The electrophysiological effects of a single intravenous administration of ivabradine were studied in patients with normal baseline electrophysiology.…”
mentioning
confidence: 99%
“…In these situations inhibition of other potassium channels may lead to unexpectedly augmented APD prolongation, resulting in proarrhythmic reactions. In previous studies the investigators found that ivabradine at 3 and 10 μM prolongs repolarization in guinea-pig papillary muscles [91,101]. Our results support the action potential lengthening effect of ivabardine also in dog and human cardiac preparations especially in case of attenuated repolarization reserve.…”
Section: Attenuated Repolarization Reservesupporting
confidence: 77%